Improving care for victims of violence in resource-poor settings such as Lusaka, Zambia: results of a low-budget intervention. Issue 2 (13th February 2015) - Schober, Michael; Mtonga, Robert; Valenti, Maria; Hametner, Stephanie
Abstract : Health professionals from Zambia and Austria conducted a low-cost intervention in Lusaka, Zambia, intended to improve care outcomes for victims of interpersonal violence (IPEV). It was designed to build on existing health and social services infrastructures. During 1 year, 174 victims of IPEV seen at the Lusaka University Hospital emergency room were interviewed by medical students. An intervention included training for medical and social service personnel and distribution at key locations of printed materials on services available to IPEV victims. Postintervention data analysis revealed that victims of IPEV had improved understanding of available social services, and victims' confidence was increased about receiving additional help and articulating health concerns. Other benefits: improved visibility, networking among partner organisations; new descriptive data about IPEV victims; improved cross-cultural understanding among medical participants. Recommendation: low-cost interventions should continue to be explored to improve care for victims of IPEV in resource-poor settings.